If you build it, they will learn: A review of models in veterinary surgical education. Issue 1 (16th July 2021) - Hunt, Julie A.; Simons, Micha C.; Anderson, Stacy L.
Abstract: Surgical skills are learned through deliberate practice, and veterinary educators are increasingly turning to models for teaching and assessing surgical skills. This review article sought to compile and review the literature specific to veterinary surgical skills models, and to discuss the themes of fidelity, educational outcomes, and validity evidence. Several literature searches using broad terms such as "veterinary surgery model, " "veterinary surgical model, " and "veterinary surgical simulator" were performed using PubMed, CAB abstracts, and Google scholar. All articles describing a model created and utilized for veterinary surgical training were included. Other review articles were used as a source for additional models. Commercially available models were found using review articles, internet browser searches, and communication with veterinary clinical skills educators. There has been an explosion of growth in the variety of small animal surgical task trainers published in the last several decades. These models teach orthopedic surgery, ligation and suturing, open celiotomy and abdominal surgery, sterilization surgeries, and minimally invasive surgeries. Some models were published with accompanying rubrics for learner assessment; these rubrics have been noted where present. Research in veterinary surgical models is expanding and becoming an area of focus for academic institutions. However, there is room for growth in the collection of validity evidence and in development of models for teaching large animal surgery, training surgical residents, and providing continuing education to practitioners. This review can assist with evaluation of current surgical models and trends, and provide a platform for additional studies and development of best practices.